2002
DOI: 10.1016/s0399-1784(01)01178-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability in the biochemical composition of sedimentary organic matter in an intertidal flat of the Galician coast (NW Spain)

Abstract: Temporal variations and spatial distribution of sedimentary organic matter composition were investigated over a one year period in an intertidal flat of the NW Spain. Sediment samples were collected from 0 to 25 cm depth, every three months, from January 1997 to January 1998 at three tidal levels (high, medium and low). Changes in the elemental and biochemical composition were assessed to gather information on temporal and spatial fluctuations in quantity and quality of sedimentary organic matter potentially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 36 publications
3
31
0
3
Order By: Relevance
“…Protein-carbohydrate ratio (PRT:CHO) is used as an index to evaluate the origin of material present in sediments and to determine the age of sedimentary organic matter (Cividanes et al 2002). This ratio was generally higher in estuarine sediments which point to the presence of low dead organic matter accumulation, probably due to the vibrant condition of estuaries.…”
Section: Discussionmentioning
confidence: 99%
“…Protein-carbohydrate ratio (PRT:CHO) is used as an index to evaluate the origin of material present in sediments and to determine the age of sedimentary organic matter (Cividanes et al 2002). This ratio was generally higher in estuarine sediments which point to the presence of low dead organic matter accumulation, probably due to the vibrant condition of estuaries.…”
Section: Discussionmentioning
confidence: 99%
“…Because TOM is usually rich in refractory compounds such as cellulose and lignin, its nutritional value for coastal animals is considered to be small (Cividanes et al 2002). Taking into account the considerable distance from the fish farm (> 3 km) and the dispersal range of aquaculturederived particulate organic matter (< 300 m from the fish cage, Yokoyama et al 2006), such organic matter appears not to be used by intertidal animals directly.…”
Section: Food Sources Of Intertidal Consumersmentioning
confidence: 99%
“…In general, terrestrial vascular plants contain large amounts of refractory compounds such as cellulose and lignin, which do not rapidly biodegrade, resulting in their accumulation in estuarine sediments. Most sedimentary organic matter is therefore of low nutritional value and not directly assimilable by benthic consumers (Cividanes et al 2002). Kimura et al (2002) assayed enzyme activities in a congeneric species of Nihonotrypaea japonica, N. harmandi, inhabiting sandflats in the outer part of Ariake Sound and suggested that labile, low-molecular-weight nitrogenous compounds in sediments serve as a principal source of nitrogen for this species.…”
Section: Characteristics Of the Shirakawa Sandflat Trophic Structurementioning
confidence: 99%